Pontocerebellar Hypoplasia Diagnosed on Autopsy: A Case Report - Stoyanov, George S (Cureus, 2020)
Pontocerebellar hypoplasia (PCH) is a diverse group of autosomal recessive genetic conditions presenting with hypoplastic changes in the brainstem, cerebellum, and spinal cord. It clinically manifests with neurological symptoms, respiratory failure, and often in a combination with other malformations of the internal organs and musculoskeletal system. In this report, we present an autopsy case report of a two-month-old female patient with blood-relative parents. The patient presented clinically with neonatal-onset respiratory failure, mild neurological symptoms, facial dysmorphism, and developmental delay. On autopsy, the cerebellum and brainstem were severely hypoplastic, and the diagnosis of PCH was established grossly. The central nervous system (CNS) revealed specific hypoplastic changes in the structures, with a decreased neuronal count, stratification disturbances of the cortex of the cerebellum, and cellular misarrangement. The morphological findings in the CNS and their associated parenchymal organ changes, even in the absence of a genetic test, were specific enough to identify PCH type 1B as the main condition.